Cross-ethnic friendship self-efficacy: A new predictor of cross-ethnic friendships among children. (October 2020) - Bagci, Sabahat C.; Cameron, Lindsey; Turner, Rhiannon N.; Morais, Catarina; Carby, Afiya; Ndhlovu, Mirina; Leney, Anaise
Across two studies ( N Study 1 = 101; N Study 2 = 262) conducted among children in the UK, we incorporate Bandura's (1986) self-efficacy theory to intergroup contact literature and introduce the new construct of cross-ethnic friendship self-efficacy (CEFSE), the belief that one can successfully form and maintain high-quality cross-ethnic friendships. Study 1 examined whether sources of CEFSE beliefs (prior contact, indirect contact, social norms, and intergroup anxiety) predicted higher quality cross-ethnic friendships through CEFSE. Study 2 replicated Study 1 and extended it by including perceived parental cross-ethnic friendship quality as a further predictor. In both studies, sources of self-efficacy beliefs (except social norms) were related to CEFSE, which predicted higher quality cross-ethnic friendships. Study 2 demonstrated that parental cross-ethnic friendships had direct and indirect associations with children's cross-ethnic friendships through sources of CEFSE and CEFSE beliefs. Findings are discussed in the light of self-efficacy and intergroup contact theories.